A melanistic form in the Genus Cyclophora spec. (Lepidoptera, Geometridae, Sterrhinae). - Pinzari, Manuela; Pinzari, Mario (Contributions to Entomology = Beiträge zur Entomologie, 2016)
A melanistic form of Cyclophora Hübner, 1822 (Lepidoptera, Geometridae, Sterrhinae) was recorded on Apennines in Central Italy. Sommario Viene descritta una forma melanica di Cyclophora Hübner, 1822 (Lepidoptera, Geometridae, Sterrhinae) del gruppo di specie punctaria trovata sull’Appennino nel Centro d’Italia. Keywords Cyclophora, melanistic form, punctaria.